Draft Seventh Five Year Plan 1985-90 and Draft Annual Plan 1985-86 (Volume I) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1985)
The Archipelago of Andaman and Nicobar Islands consists of 554 islands and rocks, big and small. Presently 36 of these Islands are inhabited with a population of 1,88,741. Most of these Islands are rather small; only 20 Islands having an area of more than 20 Sq.Kms. In actual fact, 500 of the 554 Islands cover only 7 per cent area of the Islands which is 8,293 Sq.Kms. These 500 Islands are not suitable for permanent human habitation due to their inaccessibility, non-availability of fresh water, etc.
Andaman and Nicobar Administration